2021
DOI: 10.3389/fpsyg.2021.792053
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Anxiety on Early Child Development During the COVID-19 Pandemic

Abstract: Background: Maternal prenatal anxiety is among important public health issues as it may affect child development. However, there are not enough studies to examine the impact of a mother's anxiety on the child's early development, especially up to 1 year.Objective: The present prospective cohort study aimed to examine whether maternal trait anxiety, perceived social support, and COVID-19 related fear impacted speech-language, sensory-motor, and socio-emotional development in 12 months old Serbian infants during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 111 publications
0
21
0
1
Order By: Relevance
“…The study revealed that premature delivery, height, weight, and head circumference of kids, as well as lungs and respiratory state of children with mental health and stress levels of pregnant women during the corona, are significant compared to previous corona (Nodoushan, Nazari & Alimoradi, 2020). High and moderate levels of trait anxiety during the third trimester of pregnancy (Jelicic, et al, 2021). Negative impacts on healthcare workers' job satisfaction and job-related anxiety for pregnant women during COVID-19 (Bender et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The study revealed that premature delivery, height, weight, and head circumference of kids, as well as lungs and respiratory state of children with mental health and stress levels of pregnant women during the corona, are significant compared to previous corona (Nodoushan, Nazari & Alimoradi, 2020). High and moderate levels of trait anxiety during the third trimester of pregnancy (Jelicic, et al, 2021). Negative impacts on healthcare workers' job satisfaction and job-related anxiety for pregnant women during COVID-19 (Bender et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…There was a considerable disparity between the change in getting health care and the concern because mobile applications usage by pregnant women during the COVID-19 pandemic (OzkanSat & Sozbir, 2021). During COVID-19, high levels of depression, anxiety & stress experiences of prenatal trauma, antenatal attachment, low family income, lack of physical exercise, health anxiety, sleep disorders, low social support, and having a COVID-19 infected person among relatives (Filippetti, Clarke & Rigato, 2022;Stampini et al, 2021;Khazaeian, Khazaeian & Fathnezhad-kazemi, 2021;Ravaldi et al, 2020;Jelicic, et al,2021;Colak et al, 2021;Kajdy et al, 2021&Yu, et al, 2020. High on psychological stress, who are unable to attend the delivery of critical obstetric visits and receive support from friends, family, and birthing classes (Leiker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Serbia, Jelicic's et al follow up study ( 31 ) showed medium and high levels of maternal anxiety among 142 third-semester pregnant women during the COVID-19 pandemic, and a high level of perceived social support. The study showed a positive correlation between maternal trait anxiety and child's socio-emotional status at 12 months.…”
Section: Possible Factors That May Have Affected Negatively Perinatal...mentioning
confidence: 99%
“…Une étude polonaise publiée en décembre 2021 retrouve une variabilité de 30 à 40 % des fonctions de développement (cognition, langage-parole, etc.) chez des enfants âgés de 1 an nés en ces temps de crise [25] . Une étude israélienne similaire parue en janvier 2022 retrouve des résultats allant dans le même sens [26] .…”
Section: Répercussions Sur La Santé Périnataleunclassified